Kakovost oskrbe v odnosu na oceno kakovosti vodenja kronične bolezni bolnikov s koronarno boleznijo - Tušek-Bunc, Ksenija (Acta medico-biotechnica, 2018)
Purpose: Patient-centered assessment of chronic illness care is replacing the assessment of satisfaction, which does not cover all dimensions of care. Pa- tient assessments reflect both the qual- ity of chronic illness care and provide feedback to healthcare workers about their work. The study aim was to inves- tigate the patient-centered assessment of coronary heart disease (CHD) pa- tients and its correlation with the care that was delivered. Methods: This cross-sectional study evaluated data obtained from the patient medical records and surveyed patients using the Patient Assessment of Chronic Illness Care (PACIC) ques- tionnaire. A descriptive analysis of the overall and domain-specific responses to the PACIC questionnaire was con- ducted and the association of the results with delivery of care data in the patient records was determined by Pearson's correlation coefficient. Results: The study sample included 768 of 1080 CHD patients (71,1%) at 36 family medicine practices who com- pleted the PACIC questionnaire. The mean age of the re- spondents was 68.3 +- 10.7 years and the overall PACIC score was 3.3 +- 0.9. The highest PACIC scores were deliv- ery system design (3.7), patient activation (3.7), and prob- lem solving (3.6). Follow-up received the lowest score (2.8). Quality of delivered care and PACIC scores were correlated (r = 0.10, p = 0.009). Conclusions: CHD patients highly rated all aspects of chronic care included in the PACIC questionnaire. They were least satisfied with the follow-up and coordination as- pects of chronic care. The process indicators of care were positively correlate with patient assessment of care.
Keywords: bolnik s koronarno boleznijo; bolnikova ocena vodenja kronične bolezni; coronary heart disease patients; kakovost oskrbe; patient's assessment of chronic illness care; quality of care